Do highway widening reduce congestion? - Ioulia Ossokina; Jos van Ommeren; Henk van Mourik (Tinbergen Institute, 2022)
Highway construction occurs nowadays mainly through widening of ex- isting roads rather than building new roads. This paper documents that highway widenings considerably reduce congestion in the short run, defined here as 6 years. Using longitudinal microdata from highway detector loops in the Netherlands, we find substantial travel time savings. These savings occur despite strong increases in traffic flow. The welfare benefits in the short run already cover 40% of the widenings' investment costs. Our paper contributes to an explanation why countries invest in roadworks even when the fundamental law of congestion predicts that travel savings disappear in the long run.
Keywords: R3; R33; R4; R42; H4; 330; highway widening; congestion; traffic flow; welfare effects; economic activity